A Lúcás Chan Reader: Pioneering Essays on Biblical and Asian Theological Ethics - Kalambukattu, Naiju Jose (Asian Horizons, 2017)
George Griener & James F. Keenan, ed., A Lúcás Chan Reader Pioneering Essays on Biblical and Asian Theological Ethics, Bengaluru: Dharmaram Publications, 2017. ISBN: 978-93-84964-72-6; Pages: xii+260